A Functional and Neuropathological Testing Paradigm Reveals New Disability-Based Parameters and Histological Features for P0180–190-Induced Experimental Autoimmune Neuritis in C57BL/6 Mice. Issue 2 (12th January 2017) - Gonsalvez, David G.; De Silva, Mithraka; Wood, Rhiannon J.; Giuffrida, Lauren; Kilpatrick, Trevor J.; Murray, Simon S.; Xiao, Junhua
Abstract : We assessed novel disability-based parameters and neuropathological features of the P0180 – 190 peptide-induced model of experimental autoimmune neuritis (EAN) in C57BL/6 mice. We show that functional assessments such as running capacity provide a more sensitive method for detecting alterations in disease severity than a classical clinical scoring paradigm. We performed detailed ultrastructural analysis and show for the first time that tomaculous neuropathy is a neuropathological feature of this disease model. In addition, we demonstrate that ultrastructural assessments of myelin pathology are sufficiently sensitive to detect significant differences in both mean G-ratio and mean axon diameter between mice with EAN induced with different doses of pertussis toxin. In summary, we have established a comprehensive assessment paradigm for discriminating variations in disease severity and the extent of myelin pathology in this model. Our findings indicate that this model is a powerful tool to study the pathogenesis of human peripheral demyelinating neuropathies and that this assessment paradigm could be used to determine the efficacy of potential therapies that aim to promote myelin repair and protect against nerve damage in autoimmune neuritides.